(untitled) (REMUNOM, 2025)
This study focuses on the challenges faced in implementing interdisciplinarity in the school environment. It seeks to understand how this approach can contribute to a more integrated education, while analyzing the difficulties related to teacher training and the scarcity of resources in educational institutions. Using a qualitative methodology, with an emphasis on a literature review, the paper examines the main obstacles to interdisciplinary practice and proposes strategies for overcoming them. The results indicate that interdisciplinarity favors a more meaningful pedagogical practice, promoting the collective construction of knowledge. In addition, it is a transformative tool, capable of integrating knowledge and stimulating the development of critical and reflective skills, which are fundamental for a contextualized citizen’s education.